Evaluation of the Possible Immuno-Protective Effect of Nigella Sativa Seed Oil on Cyclophosphamide- Induced Myelosuppression in Mice - Shahad A. Alsaad; Sarmed H. Kathem (College of Pharmacy University of Baghdad, 2020)
Myelosuppression is one of the serious adverse effects of cancer chemotherapy that lead to life threatening febrile neutropenia and considered a limiting factor for successful therapy. Cyclophosphamide a widely used anticancer drugs, induces severe bone marrow suppression by damaging hematopoietic stem cells. As cancer incidence expands globally, the demand for an effective myeloprotective therapy during cancer treatment is also increasing.Nigella sativa seed oil, a well-known plant extract that widely used for various health conditions. This study aims to evaluate the myeloprotective activity of Nigella sativa seed oil in cyclophosphamide-induced myelosuppression mice model. Myelosuppression induced by single intraperitoneal injection of cyclophosphamide (200 mg/kg). Animals were divided into 4 groups each with 6 mice. First group served as negative control group received only normal saline. A second group served as experimental myelosuppression model group achieved by